Association of Acculturation, Nativity and Years Living in the United States with Biobanking Among Individuals of Mexican Descent - Lopez, David S. (2014)
BACKGROUND: Biobanking is the collection of human biospecimens (tissues, blood and body fluids) and their associated clinical and outcome data. Hispanics are less likely to provide biological specimens for biobanking. The purpose of this study was to investigate the association of acculturation, nativity status and years living in the United States with participation in biobanking among individuals of Mexican descent. METHODS: Participants were 19,212 adults of Mexican descent enrolled in an ongoing population-based cohort in Houston, Texas. Participants were offered the opportunity to provide a blood, urine or saliva sample for biobanking. Acculturation was assessed with the Bidimensional Acculturation Scale for Hispanics and scores were categorized into “low acculturation,” “bicultural,” and “high-acculturation.” RESULTS: After multivariable adjustment, we found an increased likelihood of participation in biobanking among individuals classified as “bicultural” as compared with “highly acculturated” individuals (OR=1.58; 95% CI, 1.10–2.26). The associations of nativity status and years living in the United States with biobanking were not statistical significant. After stratifying by gender, the associations of acculturation, nativity status and years living in the U.S. with biobanking were not statistically significant. CONCLUSION: Although individuals of Mexican descent who were “bicultural” were more likely to participate in biobanking than individuals who were “highly acculturated,” the difference in rates of participation among acculturation categories was small. The high participation rate in biospecimen collection is likely due to extensive community-engaged research efforts. Future studies are warranted to understand individuals’ participation in biobanking. IMPACT: Community-engaged research efforts may increase Hispanics’ participation in biobanking.